Heme biosynthesis in a chicken hepatoma cell line (LMH): comparison with primary chick embryo liver cells (CELC) - Kolluri, Sridevi; Elbirt, Kimberly K.; Bonkovsky, Herbert L. (Biochimica et biophysica acta, 1999)
5-Aminolevulinic acid synthase (ALA synthase), the rate-controlling enzyme of hepatic heme biosynthesis, is feed-back repressed by heme. In the liver, chemicals such as barbiturates markedly induce ALA synthase, especially in the presence of partial defects of heme biosynthesis. The inducibility and regulation of ALA synthase have been investigated using a variety of models, including intact animals and liver cell culture systems. A widely used model that closely approximates what occurs in vivo and in humans is that of primary cultures of chick embryo liver cells (CELCs). However, CELCs have some limitations: the cells obtained are somewhat heterogeneous; isolation and culture must be repeated every week resulting in weekly variations; and cells are short-lived limiting the feasibility of time-course and transfection studies. The aim of this study was to determine if LMH cells, a chick hepatoma cell line, are a good model comparable to that of CELCs. In both cells similar patterns of response of, ALA synthase activities and mRNA levels, and of porphyrin accumulation were obtained following treatments known to affect heme biosynthesis. Similarly, heme repressed ALA synthase mRNA levels in both cell types and ALA synthase activities in LMH cells. We conclude that LMH cells are a useful model for the study of hepatic heme biosynthesis and regulation of ALA synthase.